Shelf‐Break Upwelling and Productivity Over the North Kenya Banks: The Importance of Large‐Scale Ocean Dynamics. Issue 1 (10th January 2020) - Jacobs, Z. L.; Jebri, F.; Raitsos, D. E.; Popova, E.; Srokosz, M.; Painter, S. C.; Nencioli, F.; Roberts, M.; Kamau, J.; Palmer, M.; Wihsgott, J.
Abstract: The North Kenya Banks (NKBs) have recently emerged as a new frontier for food security and could become an economically important fishery for Kenya with improved resources providing better accessibility. Little research has been done on the mechanisms supporting high fish productivity over the NKBs with information on annual and interannual environmental variability lacking. Here we use a high‐resolution, global, biogeochemical ocean model with remote sensing observations to demonstrate that the ocean circulation exerts an important control on the productivity over the NKBs. During the Northeast Monsoon, which occurs from December to February, upwelling occurs along the Kenyan coast, which is topographically enhanced over the NKBs. Additionally, enhanced upwelling events, associated with widespread cool temperatures, elevated chlorophyll, nutrients, primary production, and phytoplankton biomass, can occur over this region. Eight such modeled events, characterized by primary production exceeding 1.3 g C/m −2 /day, were found to occur during January or February from 1993–2015. Even though the upwelling is always rooted to the NKBs, the position, spatial extent, and intensity of the upwelling exhibit considerable interannual variability. The confluence zone between the Somali Current and East African Coastal Current (referred to as the Somali‐Zanzibar Confluence Zone) forms during the Northeast Monsoon and is highly variable. We present evidence that when the Somali‐Zanzibar Confluence Zone is positioned further south, it acts to enhance shelf‐edge upwelling and productivity over the NKBs. These findings provide the first indication of the environmental controls that need to be considered when developing plans for the sustainable exploitation of the NKB fishery. Plain Language Summary: The North Kenya Banks (NKBs) have recently emerged as a region capable of sustaining a rich fishery, which would boost Kenya's economy. Little research has been conducted on the environmental controls that affect these fisheries and whether there is annual variability over multiple years. Here an ocean model is used, with satellite remote sensing data, to investigate how the ocean influences this region. Specifically, the convergence of two currents during the Northeast Monsoon, the Somali Current and the East African Coastal Current, which meet near the NKBs and flow away from the coast. This induces the upwelling of cold, nutrient‐rich waters, which are brought up from depth to the surface, resulting in the NKBs being a highly productive area. The confluence of these two currents forms from December to February and its position along the Kenyan coast varies from year‐to‐year. This leads to considerable variability in the intensity, position, and spatial extent of productive waters. Productivity is enhanced over the NKBs when the confluence of the two currents is generally positioned further south. These findings provide the first indication of the environmental controls that need to be taken into account when developing plans for sustainable exploitation of the fisheries resources. Key Points: Shelf‐edge upwelling occurs over the North Kenya Banks (NKB) during the Northeast Monsoon, leading to higher productivity Strong events can occur and exhibit considerable interannual variability in intensity, position, and spatial extent The Somali‐Zanzibar Confluence Zone exerts an important control on the upwelling, which is enhanced when it is positioned further south